ANALISIS KEPUTUSAN PEMBELIAN PADA ONLINE SHOPPING SELAMA BULAN RAMADAN: STUDI KASUS PADA KONSUMEN MUSLIM DI INDONESIA - Mayang Manguri Rahayu; Rima Wahyudyanti; Andyan Pradipta Utama; Aisyah Rahmawati; Maryati Maryati (FEBI UIN Sunan Gunung Djati Bandung, 2023)
This study aims to explore the factors that influence the purchasing decisions of Muslim consumers in Indonesia during the month of Ramadan on online shopping platforms. This study uses a qualitative approach and case studies to collect data from respondents who meet the research criteria. The data collection method used is in-depth interviews and observations, which are conducted online and offline. Respondents consist of Muslim consumers and online store owners who buy and sell online during the month of Ramadan in Indonesia. The results of the study show that factors such as cultural, social, personal, and role & status factors influence the purchasing decisions of Muslim consumers in Indonesia during the month of Ramadan on online shopping platforms. The practical implication of this research is to provide useful information for e-commerce industry players to understand the preferences of Muslim consumers in Indonesia during the month of Ramadan and improve the consumer's shopping experience on online shopping platforms.